Use of focus groups in business ethics research: potential, problems and paths to progress. (July 2015) - Cowton, Christopher J.; Downs, Yvonne
Abstract : The use of focus groups is a well‐established qualitative research method in the social sciences that would seem to offer scope for a significant contribution to the advancement of knowledge and understanding in the field of business ethics. This paper explores the potential contribution of focus groups, reviews their contribution to date and makes some recommendations regarding their future use. We find that, while the use of focus groups is not extensive, they have been utilised in a non‐negligible number of studies. Focus groups are usually used as a supplementary method, often as part of the development of a research instrument. Whether used on their own or in conjunction with other methods, we find that in the majority of cases there is insufficient information for a reader to judge that the method has been carried out well and hence that the 'findings' may be trusted. Nor is it easy for future researchers to learn about the practical application of the method in business ethics contexts. We therefore recommend improved reporting in future published studies. Based on an analysis of a subsample of papers that provided a reasonable level of methodological detail, we provide further insights into, and recommendations for, the use of focus groups in business ethics research.